The effect of food type on the portion size effect in children aged 2–12 years: A systematic review and meta-analysis. (1st June 2019) - Reale, S.; Hamilton, J.; Akparibo, R.; Hetherington, M.M.; Cecil, J.E.; Caton, S.J.
Abstract: Visual cues such as plate size, amount of food served and packaging are known to influence the effects of portion size on food intake. Unit bias is a well characterised heuristic and helps to determine consumption norms. In an obesogenic environment where large portions are common place, the unit or segmentation bias may be overridden promoting overconsumption of both amorphous or unit foods. The aim of this review was to investigate the impact of offering unit or amorphous food on the portion size effect (PSE) in children aged 2–12 years. A systematic search for literature was conducted in Medline, PsycInfo and Web of Science in February 2018. A total of 1197 papers were retrieved following the searches. Twenty-one papers were included in the systematic review, of which 15 provided requisite statistical information for inclusion in a random effects meta-analysis. Increasing children's food portion size by 51–100% led to a significant increase in intake (SMD = 0.47, 95% CI: 0.39–0.55). There was no evidence to suggest that increases in consumption were related to food type (p = 0.33), child age (p = 0.47) or initial portion size served (p=0.14). Residual heterogeneity was not significant (p=0.24). The PSE was demonstrated in children aged 2–12 years when offered both unit and amorphous food items. The effect was not restricted by food type, child age or influenced by initial portion size served. Of the studies included in the meta-analysis between study heterogeneity was low suggesting minimal variation in treatment effects between studies, however, more research is required to understand the mechanisms of the PSE in preschool children. Future research should determine feasible methods to downsize portion sizes served to children.